Awareness towards stroke among high school students in Brazil:: a cross-sectional study - Rodrigues, Mateus de Sousa (2022)
BACKGROUND: Stroke is one of the main causes of death worldwide. Educational interventions on stroke are potentially effective in reducing the period between the onset of symptoms and the initial emergency medical assistance. OBJECTIVE: To assess high school students’ knowledge of stroke. DESIGN AND SETTING: Cross-sectional study conducted in high schools in northeastern Brazil. METHODS: A self-structured questionnaire survey regarding stroke awareness was applied among high school students in northeastern Brazil. Data were collected between 2018 and 2019. The chi-square test and other descriptive statistics were used. Univariate and multivariate analyses were performed using logistic regression. RESULTS: A total of 1,788 students were analyzed. Eighty percent (n = 1430) of them did not have the minimum knowledge on how to act in a stroke situation. Only 10% (n = 179) presented the ideal knowledge on how to act. Males presented lower levels of knowledge on risk factors (odds ratio, OR: 0.62%; 95% confidence interval, CI: 0.49-0.79) and signs and symptoms of stroke (OR: 0.63%; 95% CI: 0.52-0.77). Students with ≥ 10 years of schooling (OR: 1.64%; 95% CI: 1.30-2.07) demonstrated greater knowledge of signs and symptoms of stroke. Students aged 18 years (OR: 1.70%; 95% CI: 1.14-2.52) demonstrated greater knowledge than other ages regarding the telephone number of the emergency medical services. CONCLUSIONS: There was a knowledge deficit with regard to recognizing stroke and activating the emergency medical services. The findings apply to the sample investigated and suggest that there is a need for stroke educational interventions, starting in high school.